2007
DOI: 10.1254/jphs.fpj06013x
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic Receptor Subtypes Mediating Positive and Negative Inotropy in the Developing Chick Ventricle

Abstract: Abstract. The inotropic response to muscarinic receptor stimulation of isolated chick ventricular myocardium was examined at various developmental stages, and the receptor subtype involved was pharmacologically characterized. In embryonic chick ventricles, carbachol (CCh) produced positive inotropy at micromolar concentrations. In hatched chick ventricles, CCh produced negative inotropy at nanomolar concentrations. Neither positive nor negative inotropy was observed in the 19 -21-day-old embryos. Both positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Inotropic responses after carbachol stimulation of M 2 receptors have also been reported in both guinea pig left ventricular papillary muscles (Korth and Kuhlkamp, 1987; Eglen et al. , 1988) and in developing chick ventricle (Nouchi et al. , 2007).…”
Section: Introductionmentioning
confidence: 82%
“…Inotropic responses after carbachol stimulation of M 2 receptors have also been reported in both guinea pig left ventricular papillary muscles (Korth and Kuhlkamp, 1987; Eglen et al. , 1988) and in developing chick ventricle (Nouchi et al. , 2007).…”
Section: Introductionmentioning
confidence: 82%
“…It has been demonstrated that the M 1 receptor can stimulate L-type Ca 2ϩ currents in guinea pig ventricular cells (Gallo et al, 1993) and Ca 2ϩ release in rat ventricular cells (Sharma et al, 1996), causing positive inotropic effects. The M 1 receptor has also been implicated in mediating positive inotropic responses in isolated human (Du et al, 1995) and chicken myocardium (Nouchi et al, 2007). Conversely, Protas et al (1998) reported that the M 2 receptor, the same receptor subtype mediating inhibition of cardiac contractility, caused positive inotropic effects through activation of Na ϩ -Ca 2ϩ exchange and myofilament Ca 2ϩ sensitivity in guinea pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Inotropic responses to muscarinic agonists in the heart have previously been reported in both normal human ventricular trabeculae [126], guinea pig papillary muscles [127,128], embryonic chick ventricle [129,130] and rat atria [128,131], but this is the first report of such in the rat ventricle. Additionally, in normal rat heart, carbachol has been found to increase Ca 2+ sensitivity with no apparent corresponding inotropic response [132,133].…”
Section: Agonist Effects In Contracting Cells and Muscle Stripsmentioning
confidence: 89%